(untitled) (Journal of the College of Education for Women, 2019)
Predictability of School Environment in the tendency to aggressive behavior among high primary school students. This study aimed at exploring the Family and school environment predictability of the tendency to aggressive behavior among high primary school students in Irbid Second Directorate of Education. The study sample consisted of 784 male and female students in the high-primary schools of Irbid Second Directorate of Education, chosen as on random cluster sampling method. Three aspects of school environment had the predictability of the tendency to aggressive behavior. The academic orientation of students explained 9.9% of the total variation in the dependant variable while the relationships between peers explained 1.6% and the teacher-student relationship explained 0.6% of the variation. The study concluded with many recommendations including the necessity of further studies in the field of family and school environment effects on aggressive behavior among schoolchildren.